2011
DOI: 10.1111/j.2042-7158.2011.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyeongwee-San extract (KMP6): a new anti-allergic effect

Abstract: These results suggest that KMP6 may exert an anti-allergic effect through not only the inhibition of mast cell degranulation but also the inhibition of histamine synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Additionally, increased histamine tissue levels in the hypothalamus and brainstem nuclei such as the vestibular nucleus and the dorsal vagal complex are considered the primary reason for induction of motion sickness [ 83 , 85 , 86 , 87 , 88 , 89 ]. Although, like rats, mice do not vomit, motion sickness experience evokes increased levels of histamine, histamine H 1 receptor mRNA, and H 1 receptor protein expression in their hypothalamus and brainstem, which can be significantly reduced by pretreatment with hesperidin [ 83 ], a bioflavonoid that inhibits the synthesis and release of histamine from mast cells [ 90 ]. Histamine H 1 receptor blockers such as dimenhydrinate and diphenhydramine are commonly used antiemetic agents against nausea and vomiting secondary to motion sickness [ 91 , 92 , 93 ].…”
Section: Diverse Stimuli Evoke Vomiting Via Distinct Receptorsmentioning
confidence: 99%
“…Additionally, increased histamine tissue levels in the hypothalamus and brainstem nuclei such as the vestibular nucleus and the dorsal vagal complex are considered the primary reason for induction of motion sickness [ 83 , 85 , 86 , 87 , 88 , 89 ]. Although, like rats, mice do not vomit, motion sickness experience evokes increased levels of histamine, histamine H 1 receptor mRNA, and H 1 receptor protein expression in their hypothalamus and brainstem, which can be significantly reduced by pretreatment with hesperidin [ 83 ], a bioflavonoid that inhibits the synthesis and release of histamine from mast cells [ 90 ]. Histamine H 1 receptor blockers such as dimenhydrinate and diphenhydramine are commonly used antiemetic agents against nausea and vomiting secondary to motion sickness [ 91 , 92 , 93 ].…”
Section: Diverse Stimuli Evoke Vomiting Via Distinct Receptorsmentioning
confidence: 99%
“…Atractylone, which is an active constituent of Atractylodes japonica and comprises 0.72 mg in 1 g of KMP6, regulated the mast cell‐mediated allergic reactions and allergic rhinitis symptoms . Furthermore, hesperidin, which is an active constituent of Citrus sunki and comprises 5.26 mg in 1 g of KMP6, ameliorated the mast cell‐mediated allergic reactions and allergic rhinitis symptoms . Glycyrrhizic acid, which is an active constituent of Glycyrrhiza uralensis and comprises 2.60 mg in 1 g of KMP6, inhibited atopic dermatitis‐like skin lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Ketotifen was dissolved with DW and filtered through a 0.22 μm syringe filter. It has been previously reported that KMP6 suppresses allergic reactions at various concentrations ranging from 0.01 to 1 g/kg . In this study, the focus was the effect of β‐eudesmol; thus, the effects of β‐eudesmol were assessed at various doses and KMP6 was assessed at one dose (0.1 g/kg).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations